BASICS OF TITRIMETRIC METHODS OF ANALYSIS (Spectrum Journal of Innovation, Reforms and Development, 2023)
Analytical chemistry is of great practical importance in the life of modern society, since it creates tools for chemical analysis and ensures its implementation. Chemical analysis is an important means of monitoring production and assessing product quality in a number of industrial sectors, such as ferrous and non-ferrous metallurgy, mechanical engineering, production of pure and ultra-pure materials for the electronics industry, mining, chemical oil refining, petrochemical, pharmaceutical and food industries, geological service, etc. The purpose of the article is to master the basic principles of qualitative and quantitative analysis. The goal is achieved by solving a specific task for the analysis of an unknown substance, carrying out calculations using the titrimetric method of analysis and constructing the corresponding titration curve.